PERAN MEDIA VIDEO DALAM MEMAHAMI PEMBELAJARAN PECAHAN SENILAI DI UPT SD NEGERI 4 BELAWAE - KAMARUDDIN, KAMARUDDIN (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2023)
The lack of use of video media in learning that integrates it into the learning process has an impact on students' interest in learning, especially in mathematics subjects in elementary schools. This research discusses how video is a suitable medium to use to achieve learning objectives with a contextual approach. This research is qualitative research. Data was collected using observation, interview and document review techniques. Data analysis techniques consist of data reduction, data presentation and drawing conclusions. The validity of the data is carried out by triangulating the data, so that the information is between theory and facts in the field. Based on field observations, it shows that the use of video media in class IV students at UPT SDN 4 Belawae is very good with a percentage of 91.12%, the results of interviews with learning design experts show that the media is very good with a percentage of 95.00%, the results of interviews with learning media experts show that video media is very good. good with a percentage of 93.46%, individual test results show that video media is very good with a percentage of 94.23%. Based on the research results, it can be concluded that the video media for mathematics learning equivalent fractions with a contextual approach to the subject of equivalent fractions can be said to be suitable for use in the learning process. ABSTRAKKurangnya penggunaan media video dalam pembelajaran yang mengintegrasikan ke dalam proses pembelajaran, berdampak pada minat belajar siswa terutama pada mata pelajaran matematika di Sekolah Dasar. Penelitian ini membahas tentang bagaimana video sebagai media yang layak digunakan untuk mencapai tujuan pembelajaran dengan pendekatan kontekstual. Penelitian ini adalah penelitian kualitatif. Data dikumpulkan menggunakan teknik observasi, wawancara dan kajian dokumen. Teknik análisis data terdiri dari reduksi data, pemaparan data dan penarikan kesimpulan. Keabsahan data dilakukan dengan cara triangulasi data, sehingga informasi antara teori dan fakta yang ada di lapangan. Berdasarkan observasi dilapangan menunjukkan penggunaan media video pada siswa kelas IV UPT SDN 4 Belawae sangat baik dengan persentase 91,12%, hasil wawancara dengan ahli desain pembelajaran menunjukkan media sangat baik persentase 95,00%, hasil wawancara dengan ahli media pembelajaran menunjukkan media video sangat baik dengan persentase 93,46%, hasil uji perorangan menunkukkan media video sangat baik dengan persentase 94,23%. Berdasarkan hasil penelitian dapat disimpulkan bahwa media video pembelajaran matematika pecahan senilai dengan pendekatan kontekstual pada pokok bahasan pecahan senilai dapat dikatakan layak digunakan dalam proses pembelajaran.